PEMANFAATAN RUANG PUBLUIK SEBAGAI TEMPAT REKLAME DALAM SENI GRAFIS TEKNIK SERIGRAFI - VOLTA AHMAD JONNEVA, Dr. Budiwirman, M.Pd., Drs. Irwan, M.Sn. (Serupa The Journal of Art Education, 2019)
This final work aims to visualise The Use of Public Space For Billboards as a graphic art work. Showing  places that have become main targets for the display of billboards by the general society or by  companies.The stages utilised in the methodology and working process of the creation of this graphic art work are:  (1) Preparation, (2) Elaboration, (3) Synthesis, (4) Realisation of Concept, (5) Finalisation.The  visualisation of the misuse of these spaces result in 10 graphic art works with the following titles: (1)  Sedot Tiang, (2) Sedot Pohon, (3) Dibiarkan, (4) Dibentangkan, (5) Dihalangi, (6) Diikat, (7) Sedot Tiang  II, (8) Pohon Caleg, (9) Senjang and (10) Dijejerkan.Key words: utilisation, misuse, public space, billboard, graphic arts